Rheumatic diseases at the court of the Medici of Florence: the so-called "gout" of the Medici - G. Fornaciari; V. Giuffra (PAGEPress Publications, 2011)
According to the archive documents several members of the Medici family of Florence suffered from gout. The word "gout", with which the Renaissance physicians indicated pain episodes localised to hands, feet, spine and shoulders, was in general improperly used, and hint other nosological entities. A paleopathological investigation carried out on the skeletal remains of the Grand Dukes of Florence and their relatives, revealed the true nature of the diseases they suffered from, allowing to diagnose two cases of diffuse idiopathic skeletal hyperostosis (DISH), a case of rheumatoid arthritis in an advanced stage, and a case of gout.